If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -4) + -1(6x + 3) + (9x + -4) = 0 Reorder the terms: (-4 + 3x) + -1(6x + 3) + (9x + -4) = 0 Remove parenthesis around (-4 + 3x) -4 + 3x + -1(6x + 3) + (9x + -4) = 0 Reorder the terms: -4 + 3x + -1(3 + 6x) + (9x + -4) = 0 -4 + 3x + (3 * -1 + 6x * -1) + (9x + -4) = 0 -4 + 3x + (-3 + -6x) + (9x + -4) = 0 Reorder the terms: -4 + 3x + -3 + -6x + (-4 + 9x) = 0 Remove parenthesis around (-4 + 9x) -4 + 3x + -3 + -6x + -4 + 9x = 0 Reorder the terms: -4 + -3 + -4 + 3x + -6x + 9x = 0 Combine like terms: -4 + -3 = -7 -7 + -4 + 3x + -6x + 9x = 0 Combine like terms: -7 + -4 = -11 -11 + 3x + -6x + 9x = 0 Combine like terms: 3x + -6x = -3x -11 + -3x + 9x = 0 Combine like terms: -3x + 9x = 6x -11 + 6x = 0 Solving -11 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 6x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 6x = 0 + 11 6x = 0 + 11 Combine like terms: 0 + 11 = 11 6x = 11 Divide each side by '6'. x = 1.833333333 Simplifying x = 1.833333333
| 2/x=18/27 | | 9h-3=10h | | 12+3q= | | (4x+1)+(x-1)+(x+1)=180 | | T-3=9 | | t^2+3r-2=0 | | -10-6w=-8w | | 2X+2-(4X-1-9X)=6X-1 | | 19-m=23 | | -7y+5y=-10+6 | | -2n+7=-n | | 3*(-1/2)(4^2)-(-3^3)/-1/2 | | 11x-4=55 | | 4x^2+9x-4=x^2-2x | | Y-5=4(y-5)-9 | | 61-11x=17-8x | | 4r=7+5r | | 16x*9y=214 | | 5(2-0.375)-9(0.125)=4(3-0.25) | | 7/9=1/3t | | (y-5)=4y-9 | | Y-7/8=-15/17 | | log(50x+250)-log=2 | | 4x-14=8x-47-(3x-14) | | x+16=2x-13 | | 3e=3-4 | | 8x^2-7=-5-2 | | 2x+84=10 | | 7e-41=31 | | 16x+9y=214 | | 516=42 | | F(y-5)=4y-9 |